Contemporary gentrification and the right to the city - Gómez Carmona, Gabriel (Universidad de Chile. Facultad de Arquitectura y Urbanismo, 2018)
In recent decades, cities worldwide have undergone profound transformations as a result of public policies and regulations applied to their development, to the dominant model of capitalist urbanization and the complex socio-spatial changes that it experiences. These situations generate tensions between the different actors that inhabit the city, expressing themselves in citizen movements defending the urban space, the environment and the natural resources of the territory. Through a digital ethnography, the article analyzes how the defense of the urban space before the onslaught of contemporary gentrification, constitutes one of the main struggles of the citizen movements of Mexico City to assert its Right to the City. As results, it is established that this right to be enshrined in the Political Constitution of Mexico City as a fundamental human right, marks the beginning of a new stage where citizen participation may influence the direction of public policies applied to the future urban development of the city.